PENGARUH LIKUIDITAS, KEBIJAKAN HUTANG, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN SEKTOR CUSTOMER NON CYLICALS YANG TERDAFTAR DI BEI PERIODE 2019 – 2022 - Kellyn Tandrian; Jholant Bringg Luck Amelia Br Sinaga; Moses Lorensius Parlinggoman Hutabarat (Journal Accounting International Mount Hope, 2024)
This study aims to analyze the effect of liquidity, debt policy, profitability and company size on company value partially and simultaneously in companies included in the Customer Non-Cyclicals sector listed on the IDX in 2019-2022. The research method used is a quantitative research method with secondary data types. The analysis technique used is multiple linear regression analysis technique. The population is 113 companies and a purposive sampling technique is used to obtain a sample of 36 companies with a research period of 4 years, so that the number of samples is 114. The results of the study indicate that liquidity and debt policy do not have a partial effect on company value, while profitability and company size have a partial effect on company value. Simultaneously, liquidity, debt policy, company size, and profitability affect company value